Nonpharmacological Complementary Interventions for the Management of Pain after Third Molar Surgery: An Umbrella Review of Current Meta-Analyses - Parsa Firoozi; Saulo Gabriel Moreira Falci; Seong-Gon Kim; Leon A. Assael (Pain Research and Management)
Objectives. To provide a nonbiased, complete assessment of what the evidence from meta-analyses informs us about complementary and nonpharmacological treatment options for the management of pain after third molar surgery, as well as highlight any discordancy, gaps, or lack of evidence among meta-analyses. Methods. The quality of the included systematic reviews was assessed using the ROBIS tool. Corrected covered area (CCA) was calculated for pairs of similar meta-analyses to identify the amount of overlap. Reviews that were the most recent, comprehensive, and had adequate quality were considered for analyses when reviews showed a high overlap. In cases with a low amount of overlap among meta-analyses, all eligible studies were included. Also, citation matrices were constructed to address overlap. A network meta-analytical approach was adopted to rank different interventions. Results. Ten meta-analyses were included for quantitative synthesis. The quantitative analysis revealed that platelet-rich fibrin and its derivatives as well as ozone therapy reduce early and late pain better than the other complementary interventions compared to control (no complementary intervention). Conclusions. Despite the shortcomings of included meta-analyses, consolidated evidence suggests that platelet-rich-fibrin and its derivatives as well as ozone therapy outperform the other nonpharmacological complementary interventions in reducing early and late postsurgical pain following third molar extraction. However, the results should be interpreted with caution due to an unclear risk of bias and lack of firm evidence in the included meta-analyses. Moreover, there is a need for a standard protocol for the application of nonpharmacological complementary interventions.